Using the Totally Asymmetric Exclusion Process as a Model for Protein Translation - Lee, Pak Lam (Philip) (My University, 2012)
This thesis details the development of a kinetic model of translation which takes into account codon usage. The process of translation involves ribosomes decoding a sequence of codons to produce a protein. Codon usage is important in the kinetics of translation since experiments have shown that codons are processed at different rates. Codons which code for the same amino acid appear with unequal frequencies and certain synonymous codons are preferred by high expression genes. The relationship between translational efficiency and codon adaptation is explored in this thesis.
We use a simple physics model called the totally asymmetric exclusion process (TASEP) to emulate the action of ribosomes, and the decoding of mRNA in protein elongation. The simple model is parameterized by an initiation rate that determines how quickly new ribosomes are introduced onto the lattice, and the rate of motion for ribosomes associated with a site on the lattice (codon message). Based on bioinformatics studies, we assign codon speeds so that codons preferred by high expression genes are translated more quickly.
The model captures important aspects of translation like ribosome collision and codons of different speeds, and simulating it allows us to see details in dynamics which are inaccessible to experiments. TASEP has non-trivial behaviour when codon rates, and the rate of ribosome binding is varied. Slow codons can cause ribosomes to pause and may lead to a queue. We approximated real genes with its average rate, and with its slowest codons to test the salient features of how codons are used on mRNAs. We found that codon selection is important in determining when queues occur, and the ribosome density on genes. The model also shows that highly expressed genes queue later than low expression genes. The simple model gives us general insights into the translational selection of codons, and the important kinetic parameters.
Keywords: codon usage; protein translation; translation kinetics; TASEP; ribosome queueing; ribosome initiation; Biological and Chemical Physics; Physics; Biological and Chemical Physics